Translation quality of Fi’l Muta’addī in the book of Nūrul Yaqīn Fī Sīrati Sayyidil Mursalīn - Kurniawan, Rafi Akhbar; Anis, Muhammad Yunus; Syed Abdullah, Syed Nurulakla (Department of Arabic Education, Faculty of Language and Literature, Indonesia University of Education, 2023)
This study aimed to describe the forms of field muta'addi, its translation technique, and the quality of translation in the translation book of Nūrul Yaqīn Fī Sīrati Sayyidil Mursalīn. This research used a descriptive qualitative method with Spadley's (1980) data analysis. The result of this research is the finding of 276 data of file muta'addi based on its relationship with maul bih (object), which is fill muta'addi bi nafsihi and fill muta'addi bi gharial. Based on time, Al-Ghulayaini (2007) divides fill muta'addi into mādhī, mudhāri, and amr. There were 343 using translation techniques from 11 translation techniques. In this study, 214 data were translated accurately, acceptably, and with high readability. The final assessment score of translation quality is 2.84 and is categorized as high-quality translation. So, the researcher concludes that readers will be able to easily understand the text of the life journey of the Prophet Muhammad.